(untitled) (Avocetta, 2021)
This short report proposes to integrate the recent checklist of the bird species of Italy with an alien species breeding in Italy since 2011, the Alexandrine parakeet Psittacula eupatria. Two reproductive populations are currently present, one in Reggio Emilia with about 20 individuals and the other one in Rome, with 3-4 birds. Records of single free–ranging individuals of this species of Indian origin occurred in other locations of northern-central Italy, in one case recorded for several consecutive years and then disappeared. If this report will be accepted by the COI, the Italian checklist reaches a total of 20 naturalised and not yet naturalised alien birds, i.e. the 3.6% of listed species.